How to Design and Institutionalize Spending Reviews - Doherty, Laura (IMF How To Notes; How-To Note, 2022)
Spending reviews refer to the process of conducting in-depth assessments of existing public expenditure in order to identify opportunities to reduce or redirect spending from low-priority, inefficient, or ineffective spending. They offer a systemic approach to ensuring that spending is aligned with the government's policy priorities, is effective in achieving its intended objectives and is deployed efficiently. This How to Note outlines the various objectives of spending reviews and provides guidance on designing a spending review process, including the organizational architecture and roles and responsibilities of various stakeholders. It also discusses the various stages of conducting spending reviews and mechanisms for integrating their outcomes into the budget process. This note draws on lessons and experiences from countries that have established spending reviews, while recognizing that this is an emerging area for further reform.